Perbedaan Pengasuhan Balita Antara Pasangan Muda dengan Pasangan Dewasa di Daerah Istimewa Yogyakarta - sugiharti, sri sugi (Jurnal Penelitian Kesejahteraan Sosial, 2019)
The role of parents is needed for children's development. However, early marriage can affect the nutritional status of children born and growing so that they become stunted. The study was conducted with a study design crossectional. The research respondents were fertile age couples (PUS) in Sleman, Gunung Kidul and Bantul regencies with 210 respondents. Selection of three districts is based on high early marriage rates. The results showed that there were still many young couples and adult couples who had not sent their children to PAUD and family participation in BKB activities was still very low in addition to fulfilling the essential needs of infants not yet optimal. In addition, it was found that there were no significant differences between the growth of toddlers from young couples with toddlers from adult couples. Under five conditions measured by body weight per age, height per age, and body weight per height showed the same conditions between young toddlers and toddlers from adult couples. However, there are significant differences in the development of toddlers between young couples with adult partners, where toddlers from adult couples have better gross motor skills. Cross-sector commitments namely BKKBN through the Efforts of Toddler Development, Ministry of Health, Ministry of Women's Empowerment and Child Protection, as well as strengthening Primary Health Care and Posyandu are very necessary to overcome this problem. Keywords:development of toddlers; couples of childbearing age; young couple; adult couples